2022
DOI: 10.1016/j.mtbio.2021.100196
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of anti-angiogenic activity using ultrasound-activated nutlin-loaded piezoelectric nanovectors

Abstract: Angiogenesis plays a fundamental role in tumor development, as it is crucial for tumor progression, metastasis development, and invasion. In this view, anti-angiogenic therapy has received considerable attention in several cancer types in order to inhibit tumor vascularization, and the progress of nanotechnology offers opportunities to target and release anti-angiogenic agents in specific diseased areas. In this work, we showed that the angiogenic behavior of human cerebral microvascular endothelial cells can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The effect of the nanovectors on red blood cell (RBC) integrity was evaluated following a standard assay previously reported. 81 Briefly, preserved blood collected from euthanized mice (0.9–1 mL per mice, n = 3; authorization 746/2021-PR of the Italian Ministry of Health) was processed by adding 3.8% sodium citrate solution followed by centrifugation at 1000 g for 10 min, until obtainment of a clean RBC pellet, washed 3 times with 0.9% NaCl. After the last wash, RBCs were gently resuspended in saline solution to obtain a 5% RBC suspension.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of the nanovectors on red blood cell (RBC) integrity was evaluated following a standard assay previously reported. 81 Briefly, preserved blood collected from euthanized mice (0.9–1 mL per mice, n = 3; authorization 746/2021-PR of the Italian Ministry of Health) was processed by adding 3.8% sodium citrate solution followed by centrifugation at 1000 g for 10 min, until obtainment of a clean RBC pellet, washed 3 times with 0.9% NaCl. After the last wash, RBCs were gently resuspended in saline solution to obtain a 5% RBC suspension.…”
Section: Methodsmentioning
confidence: 99%
“…47 It has further been observed that under the piezoelectric effect, a polarized electric field is created, which channelized electronhole pair separation resulting in the generation of ROS intracellularly, thereby inducing apoptosis of cancer cells. 48,49 Acoustic stimuli have been reportedly applied in the brain for treating various neuropathological conditions including glioma and Alzheimer's. 50 Marino et al utilized chronic US signals at 1 MHz frequency and at an intensity of 1 W cm −2 in cells for inducing an anticancer effect in temozolomide loaded piezoelectric barium titanate NPs.…”
Section: Papermentioning
confidence: 99%
“…Ultimately, the antitumor efficacy was substantially improved, 1.8 times greater than that of single-agent chemotherapy, through the combination of P-BTO and ultrasound. In another study, Sen et al [ 79 ] reported a polymeric piezoelectric nanoparticle comprising apolipoprotein E (ApoE)-functionalized polymers loaded with the chemotherapeutic drug nutlin-3a (ApoE-Nut-PNPs), which could serve a dual purpose of chemotherapy and mild piezoelectric stimulation under ultrasound. ApoE-Nut-PNPs were shown to respond remotely to ultrasound irradiation, inducing antiangiogenic effects by inhibiting angiogenic growth factors, leading to the disrupted formation of tumor tubular vessels and ultimately resulting in reduced cell migration and invasion.…”
Section: Application Of Piezoelectric Nanomaterials Activated By Ultr...mentioning
confidence: 99%